Unravelling the factors that influence the bio-electrorecycling of carbon dioxide towards biofuels. Issue 3 (25th January 2019) - Blasco-Gómez, R.; Ramió-Pujol, S.; Bañeras, L.; Colprim, J.; Balaguer, M. D.; Puig, Sebastià
Abstract : Reliable operational procedures for the control of Microbial Electrochemical Technologies (METs) to produce suitable substrates for economically viable downstream applications were investigated. Abstract : Reliable operational procedures for the control of Microbial Electrochemical Technologies (METs) to produce suitable substrates for economically viable downstream applications were investigated. We aimed at levelling key operational conditions in a model electrosynthetic reactor in order to obtain biofuels from carbon dioxide (CO2 ). The cathodes of two tubular bioelectrochemical systems (BESs) were inoculated with an enriched culture of a carboxydotrophic strain and were operated until stable conversion of CO2 into acetate and ethanol. Both reactors averaged a production of 76 ± 9 mgethanol m −2 d −1 and 120 ± 29 mgacetate m −2 d −1, which were considered crucial for triggering the production of longer carbon chain carboxylates and alcohols in a chain elongation bioreactor. Changes in the current signal and pH were correlated with CO2 depletion and the transition from acetogenesis to solventogenesis in the enriched culture. We show that in-line monitoring of pH and electron consumption are meaningful operational variables to differentiate between the two biological processes, and open the door to develop new approaches to control the bioelectro-recycling of CO2 into biofuels by METs.